A novel model of effective thermal conductivity for gas hydrate-bearing sediments integrating the hydrate saturation and pore morphology evolution. (15th September 2022) - Wu, Didi; Li, Shuxia; Guo, Yang; Liu, Lu; Wang, Zhiqiang
Graphical abstract: Highlights: A novel ETC model integrating hydrate saturation and pore morphology evolution was proposed. Dimensionless Kersten number was expressed as 3 parameters with physical meaning. Parameters optimization by genetic algorithm was employed. Model performance comparing experimental data and other models was evaluated. Abstract: Thermal properties of gas hydrate-bearing sediments directly determine the energy efficiency during gas hydrate reservoir development. Many models of effective thermal conductivity (ETC) available in literatures could not capture the characteristic of heat conductivity accurately and match with experimental results. In this paper, based on the effective media theory, a novel model of ETC for gas hydrate-bearing sediments was developed. This novel model linking microscale hydrate pore morphology with macroscale ETC variations was validated using published laboratory data at various conditions. The values of the three parameters in the model were optimized by genetic algorithm. Results indicated that the ETC at the critical hydrate saturation reduced evidently but not significantly where the dominated pore morphology of hydrate changed from pore filling to grain coating in the excess water setting. However, the ETC was enhanced dramatically at the critical hydrate saturation in the excess gas setting. In addition, three parameters in this model govern the characteristic of ETC. The parameter S in this model revealed the critical hydrate saturation where the dominant hydrate pore morphology changed, α meant the intensity of change and β represented the symmetry of change around the critical saturation. The newly proposed model in this study offers a mechanistic understanding of the ETC in hydrate-bearing sediments considering hydrate morphology and provides a theoretical and simple expression that can be easily implemented in the numerical simulators for field-scale gas production optimization.